IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA PADA PESERTA DIDIK KELAS V SEKOLAH DASAR - Retno Sintya Dewi; Faizal Chan; Muhammad Sholeh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe how the implementation of the Pancasila student profile strengthening project for grade V Elementary School students. This research was conducted at SD 198/I Pasar Baru in the even semester of the 2024/2025 academic year. This study uses a qualitative method with a case study research type. The research data was obtained directly through data collection techniques, namely observation, interviews, and documentation of the homeroom teacher of grade V, Mrs. D, who used data validity, namely triangulation. After carrying out a series of data collection techniques, the next step is to analyze using the Milles and Huberman method, namely by reducing data, modeling data, and drawing conclusions. The results of this study indicate that the implementation of the Pancasila Student Profile Strengthening Project by teachers is guided by the Penguin Pancasila Student Profile Development Guidebook (2024). The conclusion of this study is that the homeroom teacher of grade V SDN 198/I Pasar Baru has succeeded in implementing the Pancasila student profile strengthening project with all supporting factors and finding solutions to factors that hinder the activities of the Pancasila student profile strengthening project. This can be seen from the achievement of learning objectives. The implementation of the Pancasila Student Profile Strengthening Project that has been carried out can be used as an example for other teachers in implementing similar learning.